Research on health effects of low-level ionizing radiation exposure : opportunities for the Armed Forces Radiobiology Research Institute (National Academies Press, 2014)
"It is probably only a matter of time before we witness the next event in which large numbers of people are exposed to ionizing radiation. In the past, planning a response to such an occurrence would have likely focused on the management of casualties from high-dose exposure. However, more recently, a different threat has come to the fore: accidental (through a containment breach in a nuclear power plant, for example) or intentional (via a "dirty bomb") releases of radioactivity resulting in low-dose exposure to a population. The magnitude of the health risks arising from low-dose radiation exposure is uncertain, and this uncertainty has significant economic implications for public health decision making."Research on Health Effects of Low-Level Ionizing Radiation Exposure" examines recent scientific knowledge about the human effects of exposure to low-dose radiation from medical, occupational, and environmental ionizing-radiation sources. This report is intended to provide advice to the Armed Forces Radiobiology Research Institute (AFRRI) about its role in low-dose radiation health effects research. The report identifies current research directions in radiobiological science and assesses how AFRRI programs are advancing research along these directions. The recommendations of "Research on Health Effects of Low-Level Ionizing Radiation Exposure" will provide guidance for AFRRI to build on its strengths and advance its mission while contributing to the body of scientific knowledge on the health effects of exposure to low-dose ionizing radiation"--Publisher's description.